PENDEKATAN KONSELING CLIENT-CENTERED DALAM PEMBENTUKAN KONSEP DIRI REMAJA YANG MENGIKUTI TREN DI MEDIA SOSIAL - Gebitson Allo Layuk (ADISAM PUBLISHER, 2026)
The purpose of this study is to evaluate the usefulness of the client-centered counseling approach in fostering a healthier self-concept and to investigate how adolescents’ self-concept is influenced by their involvement in social media trends. Using a qualitative descriptive approach, this study focuses on adolescents aged 15–18 years who are active on social media and engaged in digital trends. Data were collected through semi-structured interviews, observations, and documentation methods. The findings reveal that adolescents’ involvement in trends is driven by social factors, such as the desire for acceptance and recognition, as well as personal factors, such as self-expression and enjoyment. Social media interactions, particularly “likes” and comments, have a significant impact on how adolescents perceive themselves, both positively and negatively. In addition, social comparison was found to be a major factor influencing how adolescents evaluate themselves. Because it emphasizes empathy, unconditional positive regard, and genuineness, the client-centered counseling approach is considered beneficial in helping adolescents develop a more authentic understanding of themselves. Therefore, this approach may serve as an effective way to help adolescents build a healthier and more stable self-concept in the digital era.